2016
DOI: 10.13057/biodiv/d170233
|View full text |Cite
|
Sign up to set email alerts
|

Choosing native tree species for establishing man-made forest: A new perspective for sustainable forest management in changing world

Abstract: Subiakto A, Rachmat HH, Sakai C. 2016. Choosing native tree species for establishing man-made forest: A new perspective for sustainable forest management in changing world. Biodiversitas 17: 620-625. Establishment of tree plantation on degraded lands and forest clearly favored some exotic species such as Gmelina arborea, Acacia, and Eucalyptus. High productivity, less harvesting time, and deeper silvicultural knowledge are the beneficial factor for choosing those exotics species. However, the use of a wide var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 21 publications
3
22
1
4
Order By: Relevance
“…4x6 m > 3x3 m > 2x2 m). This finding is in accordance with the research by Subiakto et al (2016) concerning choice of local species for development of man-made forest, reported that average diameters of S. leprosula planted in Gunung Dahu Research Forest, ranked from the highest to the lowest were consecutively at the following planting distances: 4x4 m > 3x3 m > 2x2 m.The high average diameter at the planting distance of 4x6 m and the low average diameter at planting distance of 2x2 m is likely caused that denser population in a stand could increase competition between individuals due to limited nutrition, light, and water. According to Mawazin and Suhaendi (2012), different application of planting distances will create different light intensities which affect plant growth.…”
Section: Growth Of Diameter and Height Of Shorea Leprosulasupporting
confidence: 94%
See 1 more Smart Citation
“…4x6 m > 3x3 m > 2x2 m). This finding is in accordance with the research by Subiakto et al (2016) concerning choice of local species for development of man-made forest, reported that average diameters of S. leprosula planted in Gunung Dahu Research Forest, ranked from the highest to the lowest were consecutively at the following planting distances: 4x4 m > 3x3 m > 2x2 m.The high average diameter at the planting distance of 4x6 m and the low average diameter at planting distance of 2x2 m is likely caused that denser population in a stand could increase competition between individuals due to limited nutrition, light, and water. According to Mawazin and Suhaendi (2012), different application of planting distances will create different light intensities which affect plant growth.…”
Section: Growth Of Diameter and Height Of Shorea Leprosulasupporting
confidence: 94%
“…The results of Duncan advanced test as presented in Table 5 shows that the effect of planting distance on the growth of S. leprosula is the highest in plot with planting distance of 4x6 m as indicated with the highest average diameter and height of the plants. The lowest average diameter is exhibited in stand with planting distance of 2x2 m, whereas the lowest average height is exhibited in stand with planting distance of 3x3 m. Subiakto et al (2016) explained that the determination of planting distance depends on the objective of the forest utilization; i.e. planting dipterocarps at wider planting distance could produce greater diameter so that it is suitable to be adopted to fulfill the demand for wood aimed for construction and furniture.…”
Section: Factormentioning
confidence: 99%
“…In general, the result showed that basal area and stand volume in line planting are higher than those in total planting. The dense population and the high number of individuals in total planting technique (Table 1) increased the competition among individuals and limit the nutrients absorption, light, and water availability for each individual (Subiakto et al 2016). Novak et al (2010) suggested that growth is largely influenced by growth factors, one of which is stand density.…”
Section: Effect Of Planting Technique On Basal Area and Stand Volumementioning
confidence: 99%
“…Salah satu faktor penting agar kegiatan tersebut berhasil yaitu pemilihan jenis yang sesuai dengan kondisi tempat tumbuh. Beberapa penelitian menyarankan untuk menggunakan jenisjenis lokal selain jenis cepat tumbuh seperti jenis-jenis dari Dipterocarpaceae untuk kegiatan rehabilitasi (Appanah dan Weinland, 1996;Nussbaum dan Hoe, 1996;Otsamo et al, 1996;Hamzah et al, 2009;Sovu et al, 2009;Scheneider, 2013;Subiakto et al, 2016;Kok Loong Yeong et al, 2016). Dari 10 marga dari famili Dipterocarpaceae, kelompok Shorea merupakan kelompok marga terbesar dan terpenting yang tersebar di Indonesia untuk ditingkatkan populasi dan potensi tegakannya.…”
Section: Pendahuluanunclassified